INTERNATIONAL TOURISM AS A FORM OF INTERNATIONAL ECONOMIC AFFAIRS - Khakimova Khulkar Khamitovna (Web of Journals Publishing, 2024)
The article is devoted studying of main theoretical aspects of international tourism as a form of international economic affairs. Features of the functions – social, economic and humanitarian - are described. There are also mentioned the main principles and features on which the international tourism is based. Analyzed the terms interpretation of the modern international market of tourist service.
Keywords: international tourism, international economic affairs, tourist service, The League of nations, UN, tourist, tourism functions.